Myth of research based policy and practice - Martyn Hammersley (New Delhi Sage, 2013)
Martyn Hammersley's provocative new text interrogates the complex relationship between research, policymaking and practice, against the background of the evidence-based practice movement. Addressing a series of probing questions, this book reflects on the challenge posed by the idea that social research can directly serve policymaking and practice. Key questions explored include: - Is scientific research evidence-based as evidence for evidence-based practice?; - Is social measurement possible, and is it necessary?; - What are the criteria by which qualitative research should be judged The book also discusses the case for action research, the nature of systematic reviews, proposals for interpretive reviews, and the process of qualitative synthesis. Highly readable and undeniably relevant, this book is a valuable resource for both academics and professionals involved with research.
Keywords: Research